Robust Stability and Stabilization of Fractional-Order Interval Systems: An LMI Approach - LU, Jun-Guo; GUANRONG CHEN (IEEE transactions on automatic control, 2009)
This technical note presents necessary and sufficient conditions for the stability and stabilization of fractional-order interval systems. The results are obtained in terms of linear matrix inequalities. Two illustrative examples are given to show that our results are effective and less conservative for checking the robust stability and designing the stabilizing controller for fractional-order interval systems.